2011
DOI: 10.1007/s00394-011-0188-1
|View full text |Cite
|
Sign up to set email alerts
|

New mechanisms and the anti-inflammatory role of curcumin in obesity and obesity-related metabolic diseases

Abstract: The modulation of several cellular transduction pathways by curcumin has recently been extended to elucidate the molecular basis for obesity and obesity-related metabolic diseases. These findings might enable novel phytochemical treatment strategies as well as curcumin translation to the clinical practice for the treatment and prevention of obesity-related chronic diseases. Furthermore, the relatively low cost of curcumin, safety and proven efficacy make it advisable to include curcumin as part of healthy diet. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(155 citation statements)
references
References 68 publications
0
153
0
2
Order By: Relevance
“…A separating medium was removed and the sediment was saved for measurement on a γ-counter. The activities of AR, G6PD, GPE and GS in the liver were measured spectrophotometrically using chemical kits according to syndrome [9,28]. Moreover, previous studies have reported that curcumin can resist oxidative stress in the liver of high-fat diet (HFD)-induced diabetic rat by increasing oxygen consumption and the activity of SOD, GSH and GPx [25,29,30].…”
Section: Methodsmentioning
confidence: 99%
“…A separating medium was removed and the sediment was saved for measurement on a γ-counter. The activities of AR, G6PD, GPE and GS in the liver were measured spectrophotometrically using chemical kits according to syndrome [9,28]. Moreover, previous studies have reported that curcumin can resist oxidative stress in the liver of high-fat diet (HFD)-induced diabetic rat by increasing oxygen consumption and the activity of SOD, GSH and GPx [25,29,30].…”
Section: Methodsmentioning
confidence: 99%
“…The interactions of curcumin with several signal transduction pathways should reverse insulin resistance, hyperglycemia, hyperlipidemia, and other inflammatory symptoms associated with obesity and metabolic diseases [59]. Nevertheless, studies in humans are needed to explore the effects of curcumin in the treatment and control of metabolic abnormalities linked to obesity because knowledge at this level is still scarce.…”
Section: Curcuminmentioning
confidence: 99%
“…and shilajeet (thick exudates of the mountain during summer season) from mineral origin have been selected for testing as antiaflatoxin and antioxidant activity. All the aforementioned drugs have been reported to possess antiinflammatory and antiobesity properties [8,9] . In addition, crude haridra has been reported to be antiallergic [10] ; chitrak to be hepatoprotective [11] ;…”
mentioning
confidence: 99%